2021
DOI: 10.1097/md.0000000000026709
|View full text |Cite
|
Sign up to set email alerts
|

School closures were over-weighted against the mitigation of COVID-19 transmission

Abstract: Background: The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread wildly across the world. In March of 2020, almost all kindergarten through 12th grade (K-12) schools were closed in the United States in an urgent attempt to curb the pandemic in the absence of effective therapeutics or vaccination. Thirteen months since then, schools remain partially closed. Accumulated evidence suggests that children and adolescents are not the primary facilitators of transmission, limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 135 publications
(371 reference statements)
0
4
0
1
Order By: Relevance
“…In this sense, sexual and reproductive health must be prioritized because sexual discovery and engagement in affective and sexual relationships happen naturally throughout adolescence. Thus, it is important to con-sider that unintended teenage pregnancies may result in prolonged school closures [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, sexual and reproductive health must be prioritized because sexual discovery and engagement in affective and sexual relationships happen naturally throughout adolescence. Thus, it is important to con-sider that unintended teenage pregnancies may result in prolonged school closures [23].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, literature addressing COVID impacts on education ranges from pre-K to advanced degrees from many countries. Tan (2021), for example, conducted a meta-analysis and concluded that school closures had a negative effect on K-12 students. Mseleku (2020) noted a lack of evidence on the impact of COVID on learning outcomes and the need for research on the long and short-term impacts on students in a higher education context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tantangan pendidikan dalam hal ini adalah sulit bagi guru untuk memastikan jarak sosial, sanitasi yang layak, dan kualitas pendidikan di kelas sambil secara bersamaan berinteraksi dengan siswa yang menerima pendidikan dari jarak jauh (Tan, 2021).…”
Section: Pembahasanunclassified